2015
DOI: 10.1186/s40687-015-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar singularity of a 1D model for the 3D axisymmetric Euler equations

Abstract: We investigate the self-similar singularity of a 1D model for the 3D axisymmetric Euler equations, which approximates the dynamics of the Euler equations on the solid boundary of a cylindrical domain. We prove the existence of a discrete family of self-similar profiles for this model and analyze their far-field properties. The self-similar profiles we find are consistent with direct simulation of the model and enjoy some stability property. Introduction and main results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…A simpler 1D model with Biot-Savart law inspired by (4) has been considered in [4], where it was also proved that finite time blow up can happen for this model. In [8], more information on the structure of blow up solutions has been obtained. Existence of finite time blow up in the original Hou-Luo model has been proved in [3], and a more general argument applying to a broader class of models was presented in [5].…”
Section: Introductionmentioning
confidence: 99%
“…A simpler 1D model with Biot-Savart law inspired by (4) has been considered in [4], where it was also proved that finite time blow up can happen for this model. In [8], more information on the structure of blow up solutions has been obtained. Existence of finite time blow up in the original Hou-Luo model has been proved in [3], and a more general argument applying to a broader class of models was presented in [5].…”
Section: Introductionmentioning
confidence: 99%
“…[13]). Indeed, if in (1), (2), (3), (4) we re-label ω θ /r ≡ ω, ru θ ≡ θ, r = y, z = x, and set r = 1 in the coefficients, we obtain (10). Since in the Hou-Luo scenario, the fastest growth of vorticity is observed at the boundary of the cylinder r = 1, and in particular away from the axis, the analogy should apply.…”
Section: Derivation Of the Model Equationsmentioning
confidence: 99%
“…They established finite time blow up for a broad class of initial data. Hou and Liu [10] have described the blow up solutions in the CKY model in more detail, and showed that these solutions possess self-similar structure.…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, a new singularity formation scenario for the 3D axi-symmetric Euler equation and the 2D inviscid Boussinesq system has been proposed by Hou and Luo based on extensive numerical simulations [15,16]. As the first step to understand the scenario, models with simplified sign-definite Biot-Savart law and forcing have recently been studied in [7,6,8,12,14,18]. In this paper, we aim to bring back one of the complications encountered in the original equation -the sign changing kernel in the Biot-Savart law.
…”
mentioning
confidence: 99%